Diagrams of seasonal and daily hot water consumption by apartment buildings (ab) in the moscow region. (September 2019) - Vasilyev, Gregory; Popov, Mikhail; Dmitriev, Alexander; Vasileva, Olga; Kolesova, Marina
Abstract: The article presents an analysis of hot water consumption in apartment buildings of the Moscow region. This study was conducted based on monitoring actual data on hot water consumption by apartment buildings (AB) in Moscow and the Moscow region. The results were used to develop a computational model for the daily use of hot water in apartment buildings.